Rethinking the Selection of Pathological T-Classification for Non-Small-Cell Lung Cancer in Varying Degrees of Visceral Pleural Invasion: A SEER-Based Study - Fang, Pu; Cheng, Jiayi; Lu, Youjin; Fu, Lin (Frontiers in Surgery, 2022)
Background: The T classification of non-small-cell lung cancer (NSCLC) was upgraded from T1 to T2 when accompanied by visceral pleural invasion (VPI). However, the association between VPI and prognostic outcomes was obscure in NSCLC patients with ≤ 3cm tumor size (TS), which leaded the controversy of selection of T classification. The goal was to evaluate the effect of VPI on the prognosis of NSCLC with ≤ 3cm TS and present a modified T classification. Methods: A total of 14934 NSCLC patients without distant metastasis were recruited through a retrospective study in the SEER database. The effect of VPI on lung cancer specific survival (LCSS) was evaluated using survival curve and COX regression analysis in NSCLC patients with ≤ 3cm TS. Results: Although there was no difference of the LCSS of PL0 and PL1 patients with ≤ 2cm TS in patients without lymph node (LN) metastasis, the LCSS was lower in PL2 patients than those in PL0 (T1a: P < 0.01; T1b: P < 0.01). Moreover, the LCSS was decreased in PL1 and PL2 patients with 2 3 cm TS compared with PL0 (T1c: PL1, P < 0.01; PL2, P < 0.01) of patients without LN metastasis. No difference of LCSS was observed in patients with LN metastasis between PL0 with PL1 and PL2. Conclusion: In NSCLC patients without LN metastasis and TS ≤ 2cm, tumor with PL1 should remain defined as T1, tumor with PL2 should be defined as T2. However, 2 3 cm TS patients with PL1 or PL2 should both defined as T2. Meanwhile, ≤ 3cm TS patients with LN metastasis can be regarded as T1, whether NSCLC patients accompanied with PL1 or PL2.